2012
DOI: 10.1002/sia.4882
|View full text |Cite
|
Sign up to set email alerts
|

C60‐ToF SIMS imaging of frozen hydrated HeLa cells

Abstract: Sample preparation continues to be a major challenge for secondary ion mass spectrometry studies of biological materials. Maintaining the native hydrated state of the material is important for preserving both chemical and spatial information. Here, we discuss a method which combines a sample wash and dry protocol discussed by Berman et al1 (1) followed by plunge freezing in liquid ethane for a frozen-hydrated analysis of mammalian cells (HeLa). This method allows for the removal of the growth media and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…FH: The preparation routine was similar to that described by Piwowar et al 44 and according to Robinson and Castner. 18 First, the medium was removed.…”
Section: Frozen-hydrated Preparation Of Cellsmentioning
confidence: 99%
“…FH: The preparation routine was similar to that described by Piwowar et al 44 and according to Robinson and Castner. 18 First, the medium was removed.…”
Section: Frozen-hydrated Preparation Of Cellsmentioning
confidence: 99%
“…Kulp et al demonstrated the potential of TOF-SIMS combined with principal components analysis to distinguish chemical differences in three closely related human breast cancer cell lines [47]. In 2013, the Ewing and Winograd groups showed the potential of TOF-IMS for frozen hydrated cells after ammonium formate washing [48]. Ide et al showed that changes in lipid composition on breast cancer cell lines can be studied using TOF-SIMS [49].…”
Section: Introductionmentioning
confidence: 99%
“…The high yield of lipid based ions, combined with the subcellular lateral resolution imaging capabilities of ToF-SIMS makes it an excellent tool for studies of lipids, 1-4 cells, [5][6][7][8][9][10][11] and tissues. [12][13][14][15][16] Studies have been carried out in a variety of areas including the analysis of cancer cells, [17][18][19] cancer tissues, 20,21 muscular dystrophy, 22,23 and drug permeation into skin.…”
Section: Introductionmentioning
confidence: 99%